The effect of COVID-19 pandemic on the care of fragility hip fracture patients in the United Kingdom. A case control study in a major trauma centre. Issue 6 (December 2021) - Orfanos, Georgios; Al Kaisi, Kahlan; Jaiswal, Anuj; Lim, Justin; Youssef, Bishoy
Abstract: Introduction: Coronavirus disease 2019 is a pandemic that forced a transformation in the services provided by the National Health Service in the United Kingdom. Fragility hip fractures account for over 65, 000 cases per year in the elderly population. The study aims to assess the impact of the pandemic on fragility hip fractures. Methods: A retrospective data gather was performed to identify fragility hip fractures from the 23rd of March 2020 to the 13th of May 2020, and from the 23rd of March 2019 to the 13th of May 19. Two groups were formed and compared over their 30 day follow up. Results: The control group comprised of 97 patients, with a mean age of 82.1 years old (62–102 years) and M:F ratio of 38:59. The case group comprised of 102 patients, with a mean age of 82.3 years old (60–100 years) and a M:F ratio of 16:86. Significant differences between groups were identified for gender ( p  < 0.001), time to theatre ( p  = 0.002), length of stay ( p  < 0.001) and COVID-19 status ( p  = 0.001). In the Case group, association with mortality was found for male gender ( p  = 0.041), right side ( p  = 0.031) and COVID-19 positive test results ( p  = 0.011). Conclusion: Early surgical intervention is advocated wherever possible, and sufficient optimisation, prior to surgery whenever a COVID-19 positive patient is identified. A safe rehabilitation environment is paramount for recovery in this group of patients. Further studies are required to understand the effect of this pandemic on the fragility hip fractures. Level of evidence: Level III: Retrospective case–control study. Highlights: Early surgical intervention improves outcomes in hip fractures. Trauma theatres were available 24 h a day and were led by consultants. The measures taken helped in maintaining a similar 30 day mortality. COVID-19 patients should be adequately resuscitated prior to surgery. Having a 'COVID-19 Negative' ward for rehabilitation, improves outcomes.